Relationship between particle size in equine feces and nutritional quality of forage consumed (Veterinary Science, 2019)
In horses production and health, nutrition is critical; equines are non-ruminant herbivores and knowing the quality of forages that graze, is essential for nutritional assessment. Thus, we set out to evaluate the proportion of particle sizes of fresh feces of horses that graze different types of forages. We used the commercial instrument Nasco Digestion Analyzerto wash the samples of fresh feces and pass them through a structure of 3 stainless steel sieves with decreasing pore diameter, being: A:> 4.8 mm; B: 4.8-3.2 mm; C: 3.2-1.6 mm and D:
Keywords: equines; nutrition; growth; digestibility